ANALISIS EKONOMI PEMBANGUNAN OBJEK WISATA EKOEDUWISATA DI DESA SWARANGAN KECAMATAN JORONG TANAH LAUT - Selamet Adie Rachman; Udiansyah Udiansyah; Suyanto Suyanto (Jurnal Sylva Scienteae, 2020)
Forest is a one of natural wealth, is a the gift finite value, because could absorb carbon dioxide, produce oxygen, source foodstuffs, producer drugs, and source community economy. Government regulations about right forest entrepreneur and collection Forest products and various intensive economy in development forest exploitation, not effective if made into from logging aspect, if the forest developed to be tourist attraction will produce economic value sustainable more helpful for society and also in terms of the environment. Aim from research this is generally calculate profit and loss in development tourist attraction based environment and education. In particular for knowing magnitude investation required and income expectations which is obtained from development ecotourism. Results that obtained that is NPV as big Rp2.682.836.034 > 0, so it is declared feasible. Value IRR obtained is 37 percent, where if compared interest rate investation that is 10 percent, then this project prospective enough to development investment interest rate. Value IRR the value of 1,592 is obtained. While PP investment analysis will achieved on 3 years 9 months. If expenditure increased by 15 percent and fixed income, value NPV, IRR, BCR, and PP still showing safe and decent do it investation. If spending permanent but income decreases to 3 percent, NPV, BCR, IRR, and PP values still showing safe and worth the investment. Results from the median get value Rp 20,000 which becomes inner value WTP income costs from 100 respondents, whereas for average of WTP namely Rp19,955